2017
DOI: 10.12911/22998993/66247
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth of Curly Kale Under Salinity Stress

Abstract: Ornamental plants growing in urban areas are exposed to soil salinity that negatively affects their quality. Identifying species that retain high ornamental value despite salt stress is therefore of high practical importance. Curly kale (Brassica oleracea L. var. sabellica L.) is an attractive plant with leaves of both edible and ornamental character. The aim of the study was to evaluate a response of ornamental curly kale to different concentrations of NaCl. The study material was 'Scarlet' cultivar. The plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…The plant girths were found decreasing trends in all respective treatments except treatment T1 in which treatment plant girth was found increasing manner from 2016 to 2017. Similar trends were observed by Salachna et al, (2017) [20] , Awad et al, (2014) [3] , Aderoju and Festus (2013) [1] , Mojid (2013) [16] , Jouyban (2012) [10] . [20] , Awad et al, (2014) [3] , Aderoju and Festus (2013) [1] , Mojid (2013) [16] , Jouyban (2012) [10] , Kader (2010) [11] .…”
Section: Plant Girth or Diametersupporting
confidence: 84%
See 1 more Smart Citation
“…The plant girths were found decreasing trends in all respective treatments except treatment T1 in which treatment plant girth was found increasing manner from 2016 to 2017. Similar trends were observed by Salachna et al, (2017) [20] , Awad et al, (2014) [3] , Aderoju and Festus (2013) [1] , Mojid (2013) [16] , Jouyban (2012) [10] . [20] , Awad et al, (2014) [3] , Aderoju and Festus (2013) [1] , Mojid (2013) [16] , Jouyban (2012) [10] , Kader (2010) [11] .…”
Section: Plant Girth or Diametersupporting
confidence: 84%
“…The analysis of collected water samples were done by using AR grade regents, double distilled and adopted standard method to examinations. [6] , Jia et al, (2018) [9] , Salachna et al, (2017) [20] .…”
Section: Selection Of Study Areamentioning
confidence: 99%
“…Excessive substrate salinity causing salt stress is one of the most common abiotic stresses that negatively affect the quality of ornamental plants [4]. Exceeding tolerance threshold for salt triggers numerous adverse changes in plant growth and development [6,7]. Too high salinity limits water availability, lowers turgor and leads to inhibition of cell elongation growth, tissue necrosis, yellowing, drying and falling of leaves [8].…”
Section: Introductionmentioning
confidence: 99%
“…It causes water deficit, ion toxicity, and nutrient deficiency, leading to growth, yield and development reduction, and even to plant death (Gezi et al, 2013). Additionally, it has a negative impact on photosynthesis, water management and enzymatic activity (Salachna et al, 2017). It has been reported that salinity reduces plant productivity by reducing plant growth during the phase of osmotic stress and subsequently by inducing leaf senescence during the phase of toxicity after excessive salt accumulation in oxidative damage of lipids, proteins, and nucleic acids (Abbaspour, 2012 andAbdul Qados, 2015), resulting in the formation of reactive oxygen species(ROS) (Sudhir & Murthy, 2004;Nazar et al, 2011;He et al, 2014 andLi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%